Channel dynamics in Canyon de Chelly National Monument, Arizona, with emphasis on the effect of invasive plants - Jaeger, Kristin L., author; Wohl, Ellen E., 1962-, advisor; Cooper, David J. (David Jonathan), 1952-, committee member; Merritt, David M., committee member; Rathburn, Sara L., 1962-, committee member (Colorado State University. Libraries, 2009)
The purpose of this research was to evaluate the relative regional and local-scale influences on historic and contemporary channel change in Canyon de Chelly National Monument, Arizona, USA, with particular emphasis on the invasive, exotic plant species, tamarisk (Tamarix spp.) and Russian olive (Elaeagnus angustifolia). The stream in Canyon de Chelly is characteristic of sand-bed channels in the arid/semi-arid southwestern US, which exhibit dramatic and complex channel morphology at timescales of decades to centuries. In the last 70 years, the channel has experienced substantial narrowing and incision that is apparently concurrent with widespread establishment of tamarisk and Russian olive. To place this research within a broader context of regional trends in channel change, average rates of erosion (bank widening and bed incision) for stream channels in the southwestern US were statistically compared to southeastern US streams. Likely causes of historic and recent channel change in Canyon de Chelly were evaluated using a combination of a field-surveyed longitudinal profile of the stream channel in Canyon de Chelly, an existing analysis of channel change based on an aerial photograph record, and historical regional climate and land use information. Finally, channel response to the removal of tamarisk and Russian olive by two methods was quantified to determine which of the two methods was more effective at limiting bed incision and promoting bank widening. One method involved cutting the above-ground portion of the plant flush to the ground surface and applying an herbicide (cut-stump method). The second method involved removing the entire plant including the roots using heavy machinery (wholeplant method).
Department Head: Sally J. Sutton.